Accuracy of delta high-sensitivity troponin I in diagnosing the severity of coronary artery disease with the SYNTAX score as the gold standard - Rahman, Arifur; Latif, Sayem Bin; Ali, Mohammad Liaquat; Nasrin, Sahela; Rahman, Hasanur; Islam, Azharul; Hasan, Mahbub; Ali, Isha Abdullah; Adnan, Tanvir; Rahman, Shamimur (International Journal of Research in Medical Sciences, 2024)
Background: The SYNTAX score is a comprehensive angiographic tool that quantifies the complexity and extent of coronary artery disease (CAD) based on the number, location, and severity of lesions in the coronary arteries. This study aimed to assess the accuracy of delta high-sensitivity troponin I in diagnosing the severity of coronary artery disease with the SYNTAX score as the gold standard. Methods: This study was conducted in the Department of Cardiology, Ibrahim Cardiac Hospital & Research Institute, Bangladesh from July 2022 to June 2023. A total of 70 patients with significant delta hs-cTnI were divided into two groups: Group-A (n=36) with a delta hs-cTnI rise between >20 to 49%, and Group-B (n=34) with a delta hs-cTnI rise ≥50%. Coronary angiography was conducted, and the SYNTAX Score was calculated for both groups. Data analysis was performed using SPSS version 25.0. Results:32.4% of patients with a high-rise of delta cTnI (≥50%) had a SYNTAX score >22, compared to none of the patients with a low-rise of cTnI 20-49% (p<0.001). The delta hs-cTnI showed a significantly moderate linear correlation with the SYNTAX score (p=0.001). The optimal cut-off value for high sensitivity, with minimal compromise in specificity, was 89.0, with an area under the curve of 0.847 (p<0.001), indicating that nearly 85% of severe CAD could be accurately diagnosed with a delta hs-cTnI value of 90.0 or higher in NSTEMI patients. Conclusion: The study findings suggest that a delta hs-cTnI value of 90.0 or higher in NSTEMI patients can accurately diagnose nearly 85% of severe CAD.